Draft Annual Plan (2006-07) Proposals Volume-I Government of Manipur - Planning Commission (Planning Commission, 2005)
Manipur is one of the Border States in the north-eastern part of the country having an international boundary of about 352 kms. long stretch of land with Myanmar in the east. It is bounded by Nagaland in the north, Assam in the west and Mizoram in the south. It has a total area of 22327 sq. kms. It lies between latitude 23.8° N to 25.7° N and longitude 93.5° E to 94.8° E.
Government of Manipur, Planning Department